Fiber cross-section influence on the deposition of nanofibers on textile weaved structures - Mínguez-García, David; Capablanca, Lucía; Montava, Ignacio; Díaz-García, Pablo (Wydawnictwo Politechniki Łódzkiej, 2022)
Roughness is directly related to the increase of adhesion between surfaces. Different cross section on fibres implies different longitudinal shape of fibres, altering the roughness of filaments. In this study, a procedure to evaluate the nanofibers adhesion to the substrate has been designed. In order to test it, different cross-section shapes are evaluated to demonstrate its influence on the nanofibers net adhesion. Circular, tetralobal and trilobal fibres were tested. Focused on corroborating it, two yarns with different filament fineness were also tested. Different weights are placed on an acetate film which is placed on the nanofibers net. The pressure helps the nanofiber to move to the acetate. This procedure helps to determine the influence of fibre cross-section or roughness, demonstrating the adhesion of nanofibers net on the structures is enhanced with higher roughness.
Keywords: electrospinning; cross-section; nanofiber; adhesion; elektroprzędzenie; przekrój poprzeczny; nanowłókno; adhezja